Training for Mapping Wi-Fi Corner in Banjarmasin’s Green Open Space for Smart City Concept - Hanny Maria Caesarina; Nahdi Saubari (Comment: an International Journal of Community Development, 2020)
Smart city is one of the concepts to create sustainability in urban areas. Banjarmasin recently tried to apply this concept to create a friendly information and technology city by providing some wi-fi corners in green open spaces for the citizens. Due to this condition, it is necessary to conduct the training for mapping wi-fi corner in Banjarmasin’s green open space. This community service aims to make a wi-fi corner map in Banjarmasin and analyze its quality which can support the smart city concept. The participants are the students of Urban and Regional Planning in University of Muhammadiyah Banjarmasin. The tools and materials used along the training are GPS, mobile phones and individual laptop for each participant. The outcomes of this activity are the students capable to map the wi-fi corner of Banjarmasin’s green open space based on the connectivity and accessibility of the facility. Banjarmasin needs to provide more wi-fi corner with free access.